Allegorical making : Austin Clark, Louis MacNeice, Thomas Kinsella - Fryatt, Charlotte (Trinity College (Dublin, Ireland). School of English, 2003)
This thesis looks at the work of three poets, Austin Clarke (1896-1974), Louis MacNeice (1907-1963) and Thomas Kinsella (1928- ), in order both to raise the profile of allegory as a modality at work in twentieth-century Irish poetry in English, and to introduce more rigorous and wide-ranging theories of allegory into a field dominated by identitarian conceptions of the mode. As stated in the Introduction, it is intended as an exposition of recent allegory theory followed by three case studies which explore different aspects of that theory, and which also contribute to the critical literature on each poet, rather than as a comparative study or as a survey of allegorical expression in a twentieth-century Irish context.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin